ANALISIS INDIKATOR MUTU PELAYANAN.KESEHATAN MENURUT STANDAR PERATURAN MENTERI.KESEHATAN REPUBLIK INDONESIA NOMOR 30 TAHUN 2022 DI RSUD WALUYO JATI KRAKSAAN - dellialvi, mezzaluna; Isbandono, Prasetyo (Jurnal Inovasi Administrasi Negara Terapan (Inovant), 2023)
The achievements of the Waluyo Jati Kraksaan Hospital starting from the Waluyo Jati Kraksaan Regional General Hospital have been declared passed. Plenary Level Accreditation Hospita Accreditation Commission (KARS), Creating Innovation of Delivery Friends Services that offers safe, fast and reliable drug delivery services, Cooperation Agreement with the Probolinggo Resort Police regarding the Handling of Road Traffic Accident Victims at the Accident Situation. The purpose of this research is to describe and analyze the quality of health services. according to Standard. Regulation of the Minister of Health.Republic of Indonesia Number.30 of 2022 at Waluyo Jati Kraksaan Hospital. And describe the challenges faced by employees that can hinder efforts to implement Health Service Quality Indicators according to the Standards of the Minister of Health of the Republic of Indonesia Number 30 of 2022 at Waluyo Jati Kraksaan Hospital. The research method is qualitative research. The research focus is the Quality of Health Services according to Regulatory Standards. Minister of Health. Republic of Indonesia Number 30 of 2022 at Waluyo Jati Kraksaan Hospital and Inhibiting Factors Researchers used primary and secondary data sources. Data collection techniques are observation, interviews, and documentation. Data analysis techniques namely collection, reduction, presentation, and drawing conclusions. The results of the study are that 7 indicators are appropriate and 6 indicators are not in accordance with regulations. Minister of Health. Republic of Indonesia Number. 30 years. 2022 at Waluyo Jati Kraksaan Hospital. There are factors inhibiting the quality of health services starting from constraints on infrastructure and facilities that conflict with hospital policies, shortage of human resources, aged human resources so it is difficult to change, availability of pharmaceutical drugs, lack of supporting infrastructure such as CT scans, patient families cannot be invited to work together, Medical devices are not on standby according to standards, doctors who order drugs outside the National Formulary and don't want to be replaced, surgery scheduling that is not in accordance with SOP. Thus it can be concluded that the quality of health services is according to the Standard Regulation of the Minister of Health of the Republic of Indonesia Number 30 of 2022 at Waluyo Jati Kraksaan Hospital.   Keywords: Quality, Service, Health